Long term effect of Fertdolomite on soil, maize and wheat status on acid soil of eastern Croatia - Dario Iljkić; Vlado Kovačević; Mirta Rastija; Manda Antunović; Daniela Horvat; Marko Josipović; Ivana Varga (Journal of Central European Agriculture, 2019)
Soil acidity is one of the most common problem in cultivating plants in the open field. Dolomite enriched with nitrogen, phosphorus and potassium (trade name Fertdolomite: 24% CaO + 16% MgO + 3% N + 2.5% P2O5 + 3% K2O) was applied in autumn of 2011 in four rates (0 t*ha-1, 3.56 t*ha-1, 7.14 t*ha-1 and 14.25 t*ha-1). Aim of this experiment was testing 5-year residual impact of Fertdolomit on acid soil on maize and winter wheat grain yield and quality, as well as on changes of soil properties. Five year after application, Fertdolomit has shown positive long term effect on soil pH and hydrolytic acidity. Under Fertdolomit treatments, in 2012/2013 wheat yield was significantly increased by 22%, in 2014/2015 by 25% and in 2016/2017 by 32% in comparison with control treatment. Application of highest Fertdolomite rate significantly increased wheat grain quality (protein and wet gluten content) while impact on thousand grain weight, hectoliter mass and starch content was insignificant during all growing season. Response of maize to Fertdolomite application was considerably lower compared to wheat. Maize yield increased only for 11% in both tested years (2014 and 2016), without any significant difference for grain quality.